PENGARUH PENAMBAHAN KITOSAN DARI CANGKANG RAJUNGAN (Portonus Pelagicus) TERHADAP TOTAL MIKROBA KADAR AIR DAN MUTU ORGANOLEPTIK MIE BASAH SELAMA PENYIMPANAN - Arika Musyahadah Asy-syarifahi; Muhammad Yusuf; Agus Suyanto (Universitas Muhammadiyah Semarang, 2018)
Noodles is a food product with raw wheat flour is very popular among the people of Indonesia. Noodle products are generally used as an energy source because it has a high enough carbohydrate. Wet noodle is a product that has a short shelf life because it has a high water content. Based on the above, it is necessary to administer preservatives which can extend the shelf life of noodles and also safe for consumption, one of which is chitosan. This study aims to determine the effect of adding chitosan with some concentration and storage time to total microbes, moisture content, and organoleptic quality of wet noodles. This study used a factorial completely randomized design consisting of two factors: first factor is total chitosan concentration given (0 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm) and the second factor is storage duration (0 hours, 12 hours, 24 hours, 36 hours, 48 hours) in room temperature. The result of statistical test showed that chitosan concentration and storage time have influence to total microorganism and organoleptic, while for water content has no effect. The total microbial value at 24 hours test hour only at the concentration of chitosan 150 ppm and 200 ppm has a value that is still below the standard that has been set by SNI 01-29871992 is 1.0 x10-6. the highest water content was obtained at concentration 200 ppm hjam to-0. The results of organoleptic test of wet noodles with the addition of chitosan during storage showed the difference between wet noodles without adding chitosan (0ppm) with the addition of chitosan concentration.